The Impact of Microfinance on Female Empowerment in Egypt - Hadidi, Hala (The Arab Journal of Administration, 2018)
Microfinance has become a major instrument for the alleviation of poverty in many developing economies and a tool for female empowerment. In Egypt, it has been used to fight poverty and the country is one of the largest microfinance markets in the Arab region. At year – end 2012, the Egyptian market consisted of some 1.3 million active clients and a gross loan portfolio of US$ 324 million. Between 2005 and 2010, the number of microfinance women borrowers in Egypt increased by 47% annually from 550,000 to1.3 million, placing Egypt first among Arab countries in terms of the number of microfinance women clients. However, the impact of microfinance on women in Egypt is still questionable and many researchers are sceptical about the results of these programmes on women’s economic, political, social, and psychological improvement. This paper presents, therefore, the historical context in which the microfinance programmes have evolved in Egypt and explores the different affects they have on Egyptian women, based on a questionnaire survey of a convenience sample of 300 women currently receiving microfinance credit. The paper identifies the changes in the lives of these women and the results indicate that all microfinance variables (Loan value, Average income, and Project value) are significantly correlated with the different aspects of empowerment. Notably psychological empowerment has the highest correlation with microfinance variables, followed by social empowerment, economic empowerment, and finally political empowerment. The article proposes that changes are needed in how microfinance is delivered in Egypt in order to alleviate poverty and empower Egyptian women.